Rehabilitation in a Vegetative State: A Case Study of Medical Biological Cultural Heritage - Chen, Kai; Jiao, Yang; Sun, Yanhua (Archives of Clinical and Biomedical Research, 2025)
This study investigates a medical intangible cultural heritage case involving the rehabilitation of a patient in a vegetative state using traditional Chinese cultural techniques. The subject, Chen Biao, sustained severe traumatic brain injury from a 1957 landslide explosion and was critically ill. 1. The rescue protocol integrated eight traditional cultural techniques: (i) walking therapy for vitality preservation; (ii) familial vocal stimulation; (iii) sugar water feeding; (iv) mind-intention qigong; (v) dust scanning ritualistic; (vi) eight directions heavenly doctor ritual; (vii) nine palaces eternal light ritual; and (viii) seven stars formation layout. 2. Key implications from critical incidents: (i) workplace safety as paramount; (ii) time-sensitive bio-cultural intervention; (iii) ecological determinants of recovery. 3. Summary: (i) cultural technology can indeed cure diseases; (ii) traditional cultural techniques for diagnosis and treatment are scientific. 4. The principles of traditional cultural therapy: (i) principles of traditional cultural therapy; (ii) the mechanism of traditional cultural technology therapy; (iii) traditional cultural and technological treatment principles. This case study examines the rehabilitation of a farmer from Mugou Village, Guan'er Township, Hunyuan County, Datong City, Shanxi Province, China. Following a severe traumatic brain injury that progressed from coma to a vegetative state, the patient achieved recovery through the application of specific cultural-therapy techniques, documenting the transformative process of neurological rehabilitation.